The effects of daily alendronate, daily calcitonin and alendronate every other day on bone mineral density in osteoporotic men - AKYÜZ, GÜLSEREN DERYA; KARADAĞ SAYGI, NAİME EVRİM (INFORMA HEALTHCARE, 2007)
Objectives. Biphosphonates have been widely used in the treatment of osteoporosis, but there is not enough data on their use in men. The aim of this study is to investigate the effects of twelve months' treatment with daily 10 mg alendronate, every other day 10 mg alendronate and daily 200 IU calcitonin on bone mineral density (BMD) in men with osteoporosis. Materials and methods. 46 men with osteoporosis were randomly allocated to three groups: 15 patients in the first group received daily 10 mg alendronate and calcium (1000 mg/day), 14 patients in the second group used every other day 10 mg alendronate and calcium and 17 patients in the third group were given intranasal salmon calcitonin and calcium. At the baseline, sixth and twelfth months, BMD was measured at lumbar spine (L2-4), femoral neck and Ward's triangle zone by means of dual energy X-ray absorptiometry (LUNAR). Results. In daily and every other day alendronate and calcitonin groups there was a significant increase in BMD at lumbar spine (p = 0.004, p = 0.001, p = 0.04), but no difference at the femoral neck (p > 0.05) at the end of twelve months. When the groups were compared with each other, no significant differences in BMD levels at lumbar spine, femoral neck and Ward's triangle were found (p > 0.05).
Keywords: male osteoporosis; alendronate; calcitonin; bone mineral density; SPRAY SALMON-CALCITONIN; IDIOPATHIC OSTEOPOROSIS; RANDOMIZED-TRIAL; WOMEN; FRACTURES